The False Aneurysm - Baird, R. J. (1964)
The clinical course of 18 patients with 25 false aneurysms is reviewed. In recent years false aneurysm has been most commonly seen as a complication of arterioplastic procedures in which prosthetic arterial grafts were used. The use of indwelling needles or cannulae, particularly in patients with a wide arterial pulse pressure, can also lead to the formation of false aneurysms. In the groin, a false aneurysm is frequently mistaken for an abscess. Early diagnosis and operative repair are essential to reduce the incidence of further complications.